From the far reaches of Patagonia: new phylogenetic analyses and description of two new species of the Liolaemus fitzingerii clade (Iguania: Liolaemidae) - Abdala, Cristian Simón (2012)
Within the Liolaemus boulengeri group or "patch" group, there is a monophyletic clade named Liolaemus fitzingerii group. This clade is composed of large Liolaemus individuals, mostly psammophilus, oviparous and mainly insectivorous, distributed from central Río Negro and Neuquén to the south of Santa Cruz in Argentine Patagonia. We make a taxonomic and phylogenetic revision of the L.fitzingerii clade, describe two new species of the group, compare these results with phylogenetic hypotheses from the literature, and discuss the geographic distribution of species of the L. fitzingerii clade. The new species described here inhabit central and central-eastern Chubut Province, Argentina. These new species are easily distinguished from the other species of the L. fitzingerii group by a combination of morphological characters. The phylogenetic analyses support the description of these new species, because they are not closely related to the species with which they were previously confused. According to a new phylogenetic analysis of the L. fitzingerii clade, one of the new species, L. camarones sp. nov., has a relatively basal position within the group, whereas the other new species, L. shehuen sp. nov., is sister taxon of L. chehuachekenk. With these two new species, the L. fitzingerii clade is now composed of nine species, all of which are distributed in Argentine Patagonia.